Consumer Confidence and Residential Property Price: Evidence for Malaysia - lsmail, Nur Hafizah; Nayan, Sabri (Universiti Malaya (UM), 2021)
In recent years, real estate market has become a major interest for economists and researchers. In general, property prices are influenced by supply and demand of the real estate market. Besides that, individual's positive expectation of the real estate market would rise the demand for housing and hence, house price indexes would increase. This study provides new knowledge on how consumer confidence towards housing industry affects residential property prices in Malaysia. Previous studies on effect of consumer perception towards residential property in Malaysia are scarce. Our study differs by focusing the effect of consumer confidence on housing industry and macroeconomic drivers toward residential property prices in Malaysia over the period 2004: Ql to 2018:Q4. By using the autoregressive distributed lag (ARDL) test, the empirical results have shown the presence of long-run adjustment and indicate that consumer confidence towards housing industry and many macroeconomic variables significantly affect residential property price. From this study, we have suggested that government and policy makers should be able to understand the consumer confidence on housing industry to increase consumer satisfaction and to improve consumer sentiment towards residential property market in Malaysia.